Child Car Safety: A Parental Survey at a Tertiary Care Emergency Treatment Center in Greece. Issue 1 (January 2021) - Krepis, Panagiotis; Papasotiriou, Maria; Tsolia, Maria N.; Soldatou, Alexandra
Abstract : Objectives: This study aimed to assess parental behavior in terms of child restraint systems (CRS) use under emergency conditions while driving to the hospital's outpatient settings as well as their routine child car safety (CCS) practices. Methods: A cross-sectional survey of parents/caregivers transporting children 13 years or younger was conducted at the Emergency Treatment Center of a pediatric tertiary care center in Athens, Greece. Participants completed a questionnaire inquiring about the possession of CRS, and type and use of appropriate CRS while driving to the Emergency Treatment Center and under routine conditions. In addition, presence and type of parental education with regard to CCS and the use of seat belts among drivers were assessed. Results: Of 444 participants, 51.4% children were carried restrained, although 48.6% were fastened in an improper seat for their age, in contrast with 23.7% who travel unrestrained on a daily basis. Forward-facing restraint seats were most popular, with 53.9% total use even in children younger than 2 years or older than 4 years, whereas booster seats (9.4%) and rear-facing restraint seats (18.2%) were inappropriately disfavored. Children younger than 4 years, male drivers, and drivers who had received information on CCS had higher odds of using CRS. The proportion of those had never been provided any CCS education was 38.5%. Conclusions: Child restraint systems use was inappropriately low under routine conditions and declined even further under emergency circumstances. Most children younger than 2 years and older than 4 years traveled inappropriately restrained in a forward-facing restraint seat. Parents should be more intensively educated on child car safety seat and the proper CRS use. Abstract : Supplemental digital content is available in the text.